2019
DOI: 10.1038/s41598-019-52054-3
|View full text |Cite
|
Sign up to set email alerts
|

Coating Cutting Blades with Thin-Film Metallic Glass to Enhance Sharpness

Abstract: In this study, we sought to enhance the cutting properties of the various blades by coating them with Zr- and Fe-based thin film metallic glasses (TFMGs) to a thickness of 234–255 nm via sputter deposition. In oil-repellency/sliding tests on kitchen blades, the sliding angle and friction forces were as follows: bare blades (31.6°) and (35 µN), Ti-coated blades (20.3°) and (23.7 µN), and Z-TFMG coated blades (16.2°) and (19.2 µN). Comparisons were conducted with bare blades and those with a Teflon coating (a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Crystallographic analyses based on XRD confirmed the amorphous nature of the coating, with results similar to those reported in Ref. 12,13 . XRD patterns obtained from the TFMG coating monolayer, bare and coated blades are shown in Fig.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Crystallographic analyses based on XRD confirmed the amorphous nature of the coating, with results similar to those reported in Ref. 12,13 . XRD patterns obtained from the TFMG coating monolayer, bare and coated blades are shown in Fig.…”
Section: Resultssupporting
confidence: 86%
“…Compared with a bare blade, a blade coated with Teflon (e.g., microtome blades for thin slicing biological samples) can reduce cutting forces by ~ 80%. TFMG-coated blades can reduce cutting forces by ~ 51% without any of the peeling to which Teflon-coated blades are susceptible 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Making use of this attribute, people can improve the smoothness and sharpness of surgical blades by coating them with metallic-glass films. For instance, Chu et al [221] coated cutting blades with the Zr 53 Cu 33 Al 9 Ta 5 metallic-glass thin film, which could reduce the cutting force of microtome blades by ∼51%. Meanwhile, the metallicglass coatings can reduce the increase in the roughness of dermatome blades from 70% to only 8.6% after their use in a split-thickness skin graft surgery for hairless skin.…”
Section: Mg Coatings For Healthcarementioning
confidence: 99%
“…MG coatings feature high strength, good ductility, a smooth surface, low friction, and high hydrophobicity, exceeding those of other alloys and ceramic coatings 7,8 . The non-stick characteristics of hydrophobic materials make them ideal for medical devices, such as needles, scalpels, microtomes, dermatomes, and guide wires [8][9][10][11][12] . In previous studies, we compared the performance of different kinds of coatings 9,10 and demonstrated that MG coatings can reduce insertion/retraction resistance into porcine tissue and rubber by as much as 60-70% 9 .…”
mentioning
confidence: 99%
“…The non-stick characteristics of hydrophobic materials make them ideal for medical devices, such as needles, scalpels, microtomes, dermatomes, and guide wires [8][9][10][11][12] . In previous studies, we compared the performance of different kinds of coatings 9,10 and demonstrated that MG coatings can reduce insertion/retraction resistance into porcine tissue and rubber by as much as 60-70% 9 . Compared to bare needles, MG-treated needles have also been shown to reduce the area of needle-induced trauma by up to 44% 11 .…”
mentioning
confidence: 99%